2004 IEEE International Conference on Mobile Ad-Hoc and Sensor Systems (IEEE Cat. No.04EX975)
DOI: 10.1109/mahss.2004.1392209
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and practical query scoping in sensor networks

Abstract: A driving scenario for sensor networks is environmental monitoring: nodes gather data and send it back to a sink (i.e., a basestation with an internet connection or persistent storage) via a multi-hop tree topology. In order to form the data-gathering tree, and in order to configure the sensor nodes, the sink periodically disseminates messages into the network. For scaling, robustness, and load-balancing reasons, it is desirable to introduce multiple sinks and have nodes send data to their closest sink (under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…In Fig.6, the existing schemes in Ohtaki et al, 2006 andUtani et al, 2008, which belong to the category of ant-based routing algorithms, are denoted as MUAA and AAR, respectively. The existing scheme in Dubois-Ferriere et al, 2004 andOyman andErsoy, 2004, which describe representative data gathering for a wireless sensor network with multiple sinks, is denoted as NS. From Fig.6, it can be confirmed that our scheme denoted as Proposal in Fig.6 achieves a longer-term operation of a wireless sensor network with multiple sinks than the existing ones because it improves and balances the load of each sensor node by the communication load reduction for network control and the autonomous load-balancing data transmission.…”
Section: Experimental Results On Simulation Model With Two Sinksmentioning
confidence: 99%
“…In Fig.6, the existing schemes in Ohtaki et al, 2006 andUtani et al, 2008, which belong to the category of ant-based routing algorithms, are denoted as MUAA and AAR, respectively. The existing scheme in Dubois-Ferriere et al, 2004 andOyman andErsoy, 2004, which describe representative data gathering for a wireless sensor network with multiple sinks, is denoted as NS. From Fig.6, it can be confirmed that our scheme denoted as Proposal in Fig.6 achieves a longer-term operation of a wireless sensor network with multiple sinks than the existing ones because it improves and balances the load of each sensor node by the communication load reduction for network control and the autonomous load-balancing data transmission.…”
Section: Experimental Results On Simulation Model With Two Sinksmentioning
confidence: 99%
“…This makes the long-term observation by a wireless sensor network difficult. To solve this communication load concentration problem, a data gathering scheme for a wireless sensor network with multiple sinks has been proposed (Dubois-Ferriere et al, 2004;Oyman & Ersoy, 2004). Each sensor node, in this scheme, sends sensing data to the nearest sink node.…”
Section: Efficiency Of Data Gathering 2 Balance On Communication Loamentioning
confidence: 99%
“…1, a sink in typical sensor networks takes charge of the function as a gateway for a connection with infrastructure networks [1]. Various papers in relation to multiple static sinks also indicate the connection between a sink and an infrastructure network and the connection between all sinks as an assumption [10], [11]. Therefore, in this paper, it is assumed that each sink placed in the edge of a sensor field can communicate with the other sinks via the infrastructure networks.…”
Section: Scenario 2: Sensor Fields With Multiple Sinksmentioning
confidence: 99%